Peranan Perbankan Syariah Terhadap Pemberdayaan Ekonomi Melalui Pembiayaan Usaha Mikro, Kecil Dan Menengah - Putri, Silvia Dwi Aprilia; Siswoyo (Jurnal Perbankan Syariah, 2024)
The research aims to find out how the efforts of Bank Syariah Indonesia KCP Tuban in empowering the economy through financing Micro, Small and Medium Enterprises; the financing process for Micro, Small and Medium Enterprises carried out by Bank Syariah Indonesia KCP Tuban; conditions of the Micro, Small and Medium Enterprises sector before and after financing with Bank Syariah Indonesia KCP Tuban. This type of research is qualitative descriptive research using data collection methods by conducting interviews, notes, observations and documents related to solving existing problems. The results of the research are that there are financing facilities for UMKM, then the financing application process is in accordance with procrdures, after that the funds are disbursed to micro or UMKM customers for business capital.